2020
DOI: 10.4185/rlcs-2020-1474
|View full text |Cite
|
Sign up to set email alerts
|

Equipamiento y uso de Tecnologías de la Información y Comunicación (TIC) en los hogares españoles durante el periodo de confinamiento. Asociación con los hábitos sociales, estilo de vida y actividad física de los niños menores de 12 años

Abstract: Introducción: Las TIC están presentes en muchos hogares estableciendo cambios en la comunicación social y estilo de vida. En el año 2020 se ha declarado en España el estado de alarma con un importante periodo de confinamiento debido a la aparición de una nueva pandemia mundial COVID-19. A través de este trabajo se realiza una radiografía del equipamiento y uso de las TIC en los hogares españoles con niños menores de 12 años durante el periodo de confinamiento y cómo ese tiempo y las TIC han influido en los háb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
0
32
0
5
Order By: Relevance
“…Seventeen studies on the topic were identified. Among them, six studies were conducted in America (four in Canada [22][23][24][25], one in the USA [26], and one in Mexico [27]) and 11 were performed in Europe (five in Spain [28][29][30][31][32], two in Portugal [33,34], two in Ireland [35,36], one in the UK [37], and one in Poland [38]). Four of them had overlapping samples, but they have been included in Table 1 in the "overlapping studies" section" as they offered additional information regarding the issue examined in this paper.…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies on the topic were identified. Among them, six studies were conducted in America (four in Canada [22][23][24][25], one in the USA [26], and one in Mexico [27]) and 11 were performed in Europe (five in Spain [28][29][30][31][32], two in Portugal [33,34], two in Ireland [35,36], one in the UK [37], and one in Poland [38]). Four of them had overlapping samples, but they have been included in Table 1 in the "overlapping studies" section" as they offered additional information regarding the issue examined in this paper.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…During the lockdown measures, children's free play (under 12 years old) was negatively associated with the number of television and videogame devices at home and with time spent on smartphones, tablets, or videogame devices per day [31]. Children in Spain watched television for 80.38 min per day, played videogames for 18.78 min per day, used smart phones for 14.58 min per day and tablets 28.47 min per day [31]. Furthermore, children under 5 years old watched television for 65.33 min per day, used tablets for 17.10 min per day and mobile phones for 8.34 min per day [32].…”
Section: Outdoor and Indoor Playmentioning
confidence: 99%
“…Children's levels of physical activity in their free time largely depend on the use or enjoyment of other forms of spending their time, such as using electronic or display devices. The average number of electronic devices in households with children under 12 years of age is 6.08 devices [3], the most frequent being televisions, followed by computers, tablets, game consoles and mobile phones. In a study carried out in a sample of 837 children, the time dedicated to video games was negatively related to that for physical activity, that of learning to play an instrument, and that dedicated to artistic activities, to the family, and to free play [3].…”
Section: Physical Activity In Free and Leisure Time (Leisure-i)mentioning
confidence: 99%
“…The average number of electronic devices in households with children under 12 years of age is 6.08 devices [3], the most frequent being televisions, followed by computers, tablets, game consoles and mobile phones. In a study carried out in a sample of 837 children, the time dedicated to video games was negatively related to that for physical activity, that of learning to play an instrument, and that dedicated to artistic activities, to the family, and to free play [3]. Similar results were found in another study [40] carried out with a sample of 220 Primary school students, where it was found that those students who practiced more than 3 h of physical activity per week had fewer problems with video game addiction, so investing in programs enhancing children's adherence to sports in their free time may be an option to prevent problems related to the overuse of electronic devices or video games.…”
Section: Physical Activity In Free and Leisure Time (Leisure-i)mentioning
confidence: 99%
See 1 more Smart Citation